Mosquito fauna from the Urutaú Natural Reserve in Misiones, Argentina, with discussion about their potential as vectors of important pathogens - Muttis, Evangelina (2022)
Urutaú Natural Reserve is a protected area located in the south of Misiones province, Argentina, near Posadas Capital. This location is characterized by warm and humid climate that promote great flora and fauna diversity. Regarding the mosquito fauna, from 194 species recorded for Misiones province, 66 species are actually registered for Candelaria and 88 for Capital Department. It is known that many of them are vectors of pathogens and parasites that cause human and animal diseases. Our goal was to know the mosquito community in order to consider their importance in pathogens and parasites transmission and evaluate the performance of different capturing techniques.